Effect of temperature on fatty acid metabolism in skeletal muscle mitochondria of untrained and endurance-trained rats - Zoladz, Jerzy A.; Koziel, Agnieszka; Broniarek, Izabela; Woyda-Ploszczyca, Andrzej M.; Ogrodna, Karolina; Majerczak, Joanna; Celichowski, Jan; Szkutnik, Zbigniew; Jarmuszkiewicz, Wieslawa (PLOS ONE, 2017)
We studied the effects of various assay temperatures, representing hypothermia (25°C), normothermia (35°C), and hyperthermia (42°C), on the oxidation of lipid-derived fuels in rat skeletal muscle mitochondria of untrained and endurance-trained rats. Adult 4-month-old male Wistar rats were assigned to a training group (rats trained on a treadmill for 8 weeks) or a sedentary control group. In skeletal muscle mitochondria of both control and trained rats, an increase in the assay temperature from 25°C to 42°C was accompanied by a consistent increase in the oxidation of palmitoylcarnitine and glycerol-3-phosphate. Moreover, endurance training increased mitochondrial capacity to oxidize the lipid-derived fuels at all studied temperatures. The endurance training-induced increase in mitochondrial capacity to oxidize fatty acids was accompanied by an enhancement of mitochondrial biogenesis, as shown by the elevated expression levels of Nrf2, PGC1α, and mitochondrial marker and by the elevated expression levels of mitochondrial proteins involved in fatty acid metabolism, such as fatty acid transporter CD36, carnitine palmitoyltransferase 1A (CPT1A), and acyl-CoA dehydrogenase (ACADS). We conclude that hyperthermia enhances but hypothermia attenuates the rate of the oxidation of fatty acids and glycerol-3-phosphate in rat skeletal muscle mitochondria isolated from both untrained and trained rats. Moreover, our results indicate that endurance training up-regulates mitochondrial biogenesis markers, lipid-sustained oxidative capacity, and CD36 and CPT1A proteins involved in fatty acid transport, possibly via PGC1α and Nrf2 signaling pathways.